2023
DOI: 10.2217/fmb-2022-0143
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Aspartyl Proteases Family: A Perspective Review on the Regulation Of Fungal Pathogenesis

Abstract: Secreted aspartyl proteases (SAPs) are important enzymes for fungal pathogenicity, playing a significant role in infection and survival. This article provides insight into how SAPs facilitate the transformation of yeast cells into hyphae and engage in biofilm formation, invasion and degradation of host cells and proteins. SAPs and their isoenzymes are prevalent during fungal infections, making them a potential target for antifungal and antibiofilm therapies. By targeting SAPs, critical stages of fungal pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Our findings are aligned with the existing literature, as it is known that when C. albicans cells invade host tissues, they must surpass surface barriers like skin and mucosa [ 45 ]. In this context, Saps aid in penetration by cleaving extracellular matrix proteins such as laminin, fibronectin, collagen, and mucin [ 46 , 47 ]. Studies have also shown that C. albicans strains can both adhere to and enzymatically degrade mucins in oral cavities and the gastrointestinal tract, thereby modulating Candida populations [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are aligned with the existing literature, as it is known that when C. albicans cells invade host tissues, they must surpass surface barriers like skin and mucosa [ 45 ]. In this context, Saps aid in penetration by cleaving extracellular matrix proteins such as laminin, fibronectin, collagen, and mucin [ 46 , 47 ]. Studies have also shown that C. albicans strains can both adhere to and enzymatically degrade mucins in oral cavities and the gastrointestinal tract, thereby modulating Candida populations [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, geraniol treatment was able to downregulate the PLB-1 and SAP-1 gene expression. Those enzymes have a critical role in fungal pathogeneses, such as yeast-hyphal transformation, adhesion, and tissue invasion ( Kumar et al, 2017 ; D’Enfert et al, 2021 ; Kulshrestha and Gupta, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they could be engaged in immune evasion, adhesion, hyphal development, and biofilm formation. 20 They include 10 members that are sequentially expressed at different stages of infection and are encoded by the aspartyl proteinases (SAP) gene family. 21 The SAP2 protein has been widely studied and has been shown to play a crucial role in vaginal infection.…”
Section: Introductionmentioning
confidence: 99%